A Literature Review: Diagnosis and Management of Tympanic Membrane Perforation - Brilliantama, Fandy Akbar; Arifin, Ahmad Fuadi Hasan; Al Farosi, Ulaiya Tsania; Clarista, Silva Anggraini; Verawati Ridhoi, Khonsa Khoirunnisa (CV. Jasa Sukses Abadi, 2025)
Tympanic membrane (TM) perforation is a medical condition in which the tympanic membrane ruptures, causing a hole between the outer and middle ear. This can be caused by infection, trauma, or sudden changes in pressure resulting in symptoms such as otalgia, otorrhea, tinnitus, and vertigo. Although many perforations heal spontaneously without complications, some cases can progress to chronic conditions resulting in hearing loss, chronic otitis media, cholesteatoma, and mastoiditis. The tympanic membrane, which functions to transmit sound waves to the inner ear, may not function properly after perforation, affecting hearing. Tympanic membrane perforation can occur at any age, is more common in men and is often associated with acute otitis media at a young age and trauma at an older age. This study provides a comprehensive review of the etiology, diagnosis, and management of tympanic membrane perforation, with a focus on common and rare causes and current clinical approaches. The conclusion of this article emphasizes the importance of appropriate diagnosis and management to reduce the risk of long-term complications and improve clinical outcomes.